Mexico 2018: AMLO’s hour - Mattiace, Shannan (Revista de Ciencia Política, 2019)
In July 2018, Andrés Manuel López Obrador (AMLO) was elected President of Mexico in the largest electoral landslide in Mexico’s democratic history. As a self-proclaimed transformational candidate, AMLO made big promises in areas of great concern for Mexican citizens: anti-corruption, criminal violence and security, and the economy. Support for AMLO remained extremely strong in 2018; however, to retain that support he will need to make concrete progress in these areas. AMLO and his party coalition face formidable challenges, not the least of which are high expectations from citizens bent on major changes in governance and policy outcomes. Critics are concerned about a united executive and legislative coalition unchecked by countervailing powers, threatening a potential return to the presidencialismo of the twentieth century.